Predictors of STD Screening From the Indigenist Stress-Coping Model Among Native Adults With Binge Substance Use - Magarati, Maya; Chambers, Rachel Strom; Yenokyan, Gayane; Rosenstock, Summer; Walls, Melissa; Slimp, Anna; Larzelere, Francene; Lee, Angelita; Pinal, Laura; Tingey, Lauren (Frontiers in Public Health, 2022)
Objective: The American Indian / Alaska Native (AI/AN) population in the U.S. is thriving in spite of settler colonialist efforts of erasure. AI/AN people, however, continue to experience persistent health disparities including a disproportionate burden of substance use and sexually transmitted diseases / infections (STDs / STIs), as well as a disproportionate lack of public health STD screening services and STD prevention interventions grounded in AI/AN social contexts, experiences, and epistemologies. The present study explored how stressors and protective factors based on the Indigenist Stress Coping framework predict STD screening outcomes among Native adults. Methods: We analyzed baseline self-report data from 254 Native adults ages 18-55 years with recent binge substance use who were enrolled in an evaluation of “EMPWR,” a two-session STD risk reduction program in a rural, reservation-based community in the U.S. Southwest. Logistic regression models with robust variance were used to estimate odds ratios of lifetime STD testing for the theoretical stressors and cultural buffers. Results: A little over half the sample were males (52.5%, n=136), with a mean age of 33.6 years (SD=8.8). The majority (76.7%, n=195) reported having ever been screened for STD in their life. Discrimination score were significantly associated with lifetime STD testing: The higher discrimination was associated with lower odds of STD testing in the fully adjusted model (aOR =0.40, 95%CI: 0.18, 0.92). The effects of AI/AN-specific cultural buffer such as participation in traditional practices on STD testing outcomes was in the expected positive direction, even though the association was not statistically significant. Household size was significantly associated with STD screening: The higher the number of people lived together in the house, the higher the odds of STD testing in the fully adjusted model (aOR=1.19, 95%CI: 1.04, 1.38). Conclusion: Our findings suggest that STD prevention programs should take into consideration AI/AN-specific historical traumatic stressors such as lifetime discrimination encounters and how these interact to drive or discourage sexual health services at local clinics. In addition, larger household size may be a protective factor functioning as a form of social support, and the extended family’s role should be taken into consideration.